SEISMICITY LOCALIZATION BEFORE LARGE KAMCHATKAN EARTHQUAKES - Zavyalov A.D.; Nikitin Y.V. (My University, 2000)
Gradual restriction of fracturing toward the plane of the future main rupture and its subsequent localization near this plane are qualitatively described by the avalanche unstable-fracturing model of earthquake precursors. Localization of fracturing was recorded in the laboratory during tests of rock specimens. A study of this effect during the precursory seismicity of large earthquakes occurring in the Kamchatka seismic region is reported. The examined parameters were the distance R from the center of mass of the hypocenter points to the first nodal plane of the relevant earthquake and the distribution of seismogenic rupture density P(s) for their behavior in time and space. These quantities were combined into a single parameter, S = RP(c), which shows the closeness of seismic events to the nodal plane of a large earthquake and the degree of cracking in the medium. The results suggest that seismicity tends to be localized near the nodal plane of a future main rupture, the localization volume probably specifying the location of the future high-magnitude earthquake hypocenter (the place of rupture nucleation). The main event is followed by aftershocks occurring in a region of lower values of P(c) close to the mainshock hypocenter, thus terminating the failure process.